Governing a Dual Executive – Agents and Stewards in the Swedish Management Regime - Wockelberg, Helena; Ahlbäck Öberg, Shirin (Scandinavian Journal of Public Administration, 2025)
This article analyses the tension between democratic and constitutional demands for control over delegated mandates and contemporary trust-oriented management policies of the Swedish national executive. Competing management ideals are here analyzed in terms of control-oriented Principal-Agent (PA) models and trust-oriented Principal-Steward (PS) models. The case is studied from within three perspectives that constitute core dimensions of the Swedish management regime: the constitutional preconditions for government-agency relations, the application of formal management instruments, and the role that informal instruments play in the management regime. We find that the Swedish management regime is PA-oriented at its core – constitutionally and in terms of the choice of management model for agencies – but featuring PS-oriented financial and policy autonomy for central government agencies. Informal steering is prohibited but the dominant interpretation of the constitution is that it allows PS-oriented informal contacts that are equal, cooperative exchanges of information, including efforts to clarify formal steering. We question the validity of this conclusion as clarification of steering is too closely related to steering to be reliably something else. Thus, the role of informal contacts is formally and rhetorically reserved for PS-oriented use, that is, interaction on equal and cooperative terms, but in practice also entails PA-oriented top down control.